Randomized, sham-controlled, clinical trial of repetitive transcranial magnetic stimulation for patients with Alzheimer’s dementia in Japan - Saitoh, Youichi; Hosomi, Koichi; Mano, Tomoo; Takeya, Yasushi; Tagami, Shinji; Mori, Nobuhiko; Matsugi, Akiyoshi; Jono, Yasutomo; Harada, Hideaki; Yamada, Tomomi; Miyake, Akimitsu (Frontiers in Aging Neuroscience, 2022)
Background Several medications have been applied to Alzheimer’s dementia patients (AD) but their efficacies have been insufficient. The efficacy and safety of 4 weeks of repetitive transcranial magnetic stimulation (rTMS) in Japanese AD were evaluated in this exploratory clinical trial. Methods Forty-two patients, aged 60–93 years (average, 76.4 years), who were taking medication (> 6 months) and had Mini-Mental State Examination (MMSE) scores ≤ 25 and Clinical Dementia Rating Scale scores (CDR-J) of 1 or 2, were enrolled in this single-center, prospective, randomized, three-arm study [i.e., 120% resting motor threshold (120% RMT), 90% RMT for the bilateral dorsolateral prefrontal cortex, and Sham]. Alzheimer’s Disease Assessment Scale-Japanese Cognitive (ADAS-J cog), Montreal Cognitive Assessment (MoCA-J), Clinical Global Impression of Change (CGIC), Neuropsychiatric inventory (NPI), and EuroQOL 5 Dimensions 5-Level (EQ-5D-5L) were administered. The primary endpoint was the mean change from baseline in the MMSE score (week 4). An active rTMS session involved applying 15 trains bilaterally (40 pulses/train at 10 Hz; intertrain interval, 26 s). Participants received ≥ 8 interventions within the first 2 weeks and at least one intervention weekly in the 3rd and 4th weeks. Full Analysis set (FAS) included 40 patients [120% RMT (n = 15), 90% RMT (n = 13), and Sham (n = 12)]. Results In the FAS, MMSE, ADAS-J cog, MoCA-J, CDR-J, CGIC, NPI, and EQ-5D-5L scores between the three groups were not significantly different. Two patients were erroneously switched between the 120% RMT and 90% RMT groups, therefore, “as treated” patients were mainly analyzed. Post hoc analysis revealed significant treatment efficacy in participants with MMSE scores ≥ 15, favoring the 120% RMT group over the Sham group. Responder analysis revealed 41.7% of the 120% RMT group had a ≥ 3-point improvement in the ADAS-J cog versus 0% in the Sham group (Fisher’s exact test, p = 0.045). The MoCA-J showed the same tendency but was not significant. Efficacy disappeared in week 20, based on the ADAS-cog and MoCA-J. No intervention-related serious adverse events occurred. Conclusion This paper is the first report of using rTMS in Japanese AD patients. The treatment seems safe and moderate-mild stage AD should be target population of pivotal clinical trial with 120% RMT rTMS.